Prarancangan Pabrik Selulosa Dari Tandan Kosong Kelapa Sawit dengan Proses Soda-Nitrat Kapasitas 50.000 ton/tahun - , DIAN PURNAMASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Process production of cellulose from Palm Empty Fruit Bunches consists of two main process, hydrolysis of pentosan and delignification. The hydrolysis of pentosan takes place in continuous stirred tank reactor (CSTR) at isothermal condition at temperature 150 oC and pressure 7 atm. The delignification process takes place in digester with screw impeller at 160 oC and pressure of 7 atm. The cellulose plant with capacity 50,000 tonnes/year will be established in Medan, North Sumatera. It needs area 45,300 m2 and 181 employees. The plant needs main raw materials of Palm Empty Fruit Bunches 144,032.79 tonnes/year, sodium hydroxide 15,832.08 tonnes/year, and HNO3 30% solution 104,830.74 tonnes/year. The utilities used include water at the rate of 4,562,035 tonnes/year gotten from Deli River at Deli Serdang, Medan